G505(P) Internal carotid artery abscess and narrowing; a rare cause of stroke in children – A case report. (27th April 2016) - Sharma, V; Sinha, A; Shefler, A
Abstract : Introduction: Stroke in children is uncommon in general and stroke secondary to internal carotid artery abscess and narrowing has only rarely been reported. We could find only two similar case reports in children on reviewing the literature. Case: We report a case of cerebral infarction secondary to internal carotid artery abscess and narrowing. A two year old boy was admitted to hospital with a short history of fever, vomiting and lethargy. He had received oral antibiotics for four days for tonsillitis. A clinical diagnosis of meningitis was made. CSF Examination confirmed the diagnosis of meningitis with WBC 265 × 10 9 /L of which 50% were polymorphs. He was treated with IV Ceftriaxone. Blood and CSF cultures remained sterile. On day six of admission, he developed a left hemiparesis. MRI/MRA scan showed infarction in the right MCA area. It also showed abscess fluid wrapped around and constricting right internal carotid artery. He was transferred to the Paediatric Critical Care (PCC) Unit. Whilst in PICU he developed further hypertonia, fisting and weakness on the left side as well as seizures. A repeat MRI demonstrated ischemia in the right MCA region, base of skull osteomyelitis and bilateral otitis media. He was treated with intravenous immunoglobins and steroids for five days and intravenous antibiotics for six weeks. Conclusion: We hypothesised that he developed stroke secondary to thrombus originated from internal carotid artery secondary to carotid artery abscess and narrowing. This rare complication should be considered in children with focal neurological signs in the context of meningitis.